Does statins promote vascular calcification in chronic kidney disease?. (February 2017) - Chen, Zhimin; Qureshi, Abdul Rashid; Parini, Paolo; Hurt‐Camejo, Eva; Ripsweden, Jonaz; Brismar, Torkel B.; Barany, Peter; Jaminon, Armand M.; Schurgers, Leon J.; Heimbürger, Olof; Lindholm, Bengt; Stenvinkel, Peter
Abstract: Background: In end‐stage renal disease (ESRD), coronary artery calcification (CAC) and inflammation contribute to cardiovascular disease (CVD). Statins do not improve survival in patients with ESRD, and their effect on vascular calcification is unclear. We explored associations between CAC, inflammatory biomarkers, statins and mortality in ESRD. Materials and methods: In 240 patients with ESRD (63% males; median age 56 years) from cohorts including 86 recipients of living donor kidney transplant (LD‐Rtx), 96 incident dialysis patients and 58 prevalent peritoneal dialysis patients, associations of CAC score (Agatston Units, AUs), interleukin‐6 (IL‐6) with high‐sensitivity C‐reactive protein (hsCRP), tumour necrosis factor (TNF), use of statins and all‐cause mortality were analysed. Cardiac CT was repeated in 35 patients after 1·5 years of renal replacement therapy. In vitro, human vascular smooth muscle cells (hVSMCs) were used to measure vitamin K metabolism. Results: Among 240 patients, 129 (53%) had a CAC score > 100 AUs. Multivariate analysis revealed that independent predictors of 1‐SD higher CAC score were age, male gender, diabetes and use of statins. The association between CAC score and mortality remained significant after adjustment for age, gender, diabetes, CVD, use of statins, protein‐energy wasting and inflammation. Repeated CAC imaging in 35 patients showed that statin therapy was associated with greater progression of CAC. In vitro synthesis of menaquinone‐4 by hVSMCs was significantly impaired by statins. Conclusion: Elevated CAC score is a mortality risk factor in ESRD independent of inflammation. Future studies should resolve if statins promote vascular calcification and inhibition of vitamin K synthesis in the uremic milieu.